Principles of treatment planning for compromised first permanent molars in mixed dentition period: A review article - Behrad Tanbakuchi; Sepideh Arab (Tehran University of Medical Sciences, 2017)
Background and Aims: The first permanent molar is susceptible to caries, endodontic complications and developmental anomalies. Compromised teeth with poor prognosis could cause the clinician to face dilemmas. The aim of this review article was to assess recent guidelines on the treatment planning of compromised first permanent molars in mixed dentition period. Materials and Methods: The design of the study was based on review of literature by searching the MEDLINE, Web of science and Google scholar. Key words (permanent first molar, extraction, treatment plan) were used. This search was limited to the English articles published after the year 2000. Conclusion: A number of factors influenced decision-making process regarding compromised first permanent molars including the restorative status of the tooth, dental age of the patient, degree of crowding and occlusal relationships were assessed. The ideal time for removal of these teeth was 8-9 years of age. However, the current evidence for managing compromised first permanent molars demands clinical trials.